Pengaruh Pengetahuan dan Sikap terhadap Perilaku Penggunaan APD pada Buruh Tani Tembakau (Studi di PTPN X Kabupaten Jember) - Nurina Aprilya; F.X. Ady Soesetijo; Hadi Prayitno (Multidisciplinary Journal, 2020)
The utilising of Personal Protective Equipment (PPE) is necessary in order to prevent both accident and workrelated illness among farmer, such as Green Tobacco Sickness (GTS) within tobacco farmer. The aim of this study was to understand the role of knowledge and attitude toward the PPE usage behavior. This was observational analytics study with cross sectional design. The participant of this study was 175 farmers. In addition, statistical analysis was performed by logistic regression through SPSS. This study found that the significant level of knowledge and attitude toward PPE usage behavior is 0.030 and 0.000, respectively. It indicated that there is correlation between both knowledge and attitude toward PPE usage behavior among farmer. Keyword: Knowledge, Attitude, PPE utilising behavior